PENGARUH MEKANISME CORPORATE GOVERNANCE, PENGUNGKAPAN SOSIAL, DAN PERINGKAT CGPI TERHADAP KUALITAS LABA - Eko Budi Santoso; Meiliana Tan (Jurnal Riset Akuntansi dan Keuangan, 2011)
The objective of this research is to examine the influence of several corporate governance mechanisms, namely managerial ownership and institutional ownership; information of corporate social responsibility (CSR) disclosed in the companies’ annual reports, and the rate of corporate governance perception index (CGPI) on earnings quality (measured by earning response coefficient/ERC). The sample of this research is all private company listed on Indonesia Stock Exchange (IDX) since 1993 which include the top ten and non-top ten of corporate governance perception index (CGPI) rate in 2002-2008, except 2007. The number of sample is 53 samples from 28 companies collected. By using regression analysis, the result of this research show that : (a) managerial ownership has no influence on earnings quality;(b) institutional ownership has no influence on earnings quality; (c) the level of CSR disclosure has influence on earnings quality; and (d) the corporate governance perception index (CGPI) rate has no influence on earnings quality in five percent level of significance,but it is significant in ten percent level of significance. This result indicates that investors asses the CSR information disclosed by the companies in their annual reports for their investment decision.Keywords: corporate governance mechanism, corporate social responsibility, earning quality